Microscopic investigation of layer growth during olivine bed material aging during indirect gasification of biomass. (15th April 2020) - Faust, Robin; Sattari, Mohammad; Maric, Jelena; Seemann, Martin; Knutsson, Pavleta
Abstract: Olivine bed material used in an aging experiment for indirect gasification in the Chalmers 2–4-MWth DFB gasifier was investigated with the aim to determine the mechanism of layer formation around the particles upon exposure to gasification conditions. The collected samples were exposed for 1, 2 and 4 days. The development of ash layer around the bed material particles was studied with different analysis methods. Formation of Ca3 Mg(SiO4 )2 and MgO was confirmed by X-ray diffraction (XRD). Cross-sections of the bed material samples were prepared using Broad Ion Beam (BIB) milling and were further analyzed with Scanning Electron Microscopy coupled with Energy Dispersive X-ray spectroscopy (SEM-EDS). The analysis of the produced cross-sections revealed the formation of a Mg-rich surface layer on top of the Ca-rich ash layer. Minor amounts of K were also found near the sample surface. Based on the results from the characterization techniques, a reaction mechanism involving the transition of Mg2 SiO4 with CaO to MgO and Ca3 Mg(SiO4 )2 was suggested which was confirmed by equilibrium calculations. This mechanism was supported by Transmission Electron Microscopy (TEM) analysis where diffraction patterns corresponding to MgO were found. TEM-EDS line-scan revealed the presence of ash components in the ash layer such as P and Ti at locations coinciding with high levels of Ca which indicates the formation of Ca3 (PO4 )2 and CaTiO3 . The results presented provide detailed information on the composition of the ash layer which can be used to fully understand the mechanism responsible for the formation of catalytically active ash layers.